TRAFFIC ACCIDENT BLACKSPOT IDENTIFICATION AND AMBULANCE FASTEST ROUTE MOBILIZATION PROCESS FOR THE CITY OF SURAKARTA - Budiharto, Utoyo; P. Saido, Agus; Syafi’i, Syafi’i (Jurnal Transportasi, 2012)
Quickly and precisely treatment in traffic accident is one way to avoid the risk of death victims. Therefore, itâs necessary to determine the fastest route from the traffic accident locations to the nearest hospital. The research objective was to determine the traffic accident blackspot of Surakarta city, the referral hospitals and the ambulance fastest route using GIS program. Determination of traffic accident blackspot used three methods, that are kernel density estimation, cluster and outlier analysis. Method of determining the fastest route mobilization is network analyst tool. Determination of the fastest route mobilization based on travel time. According to an analysis, there are 15 locations of traffic accident blackspots in Surakarta city. A referral hospitals in Surakarta city are Brayat Minulya, Dr. Moewardi, Dr. Oen, Kasih Ibu, Kustati, Panti Waluyo and PKU Muhammadiyah hospital. Mobilization route of the accidents victim has an average of travel time about 4.84 minutes.Keywords: traffic accident blackspot, hospital, GIS, fastest route